2012
DOI: 10.1007/s10880-011-9281-0
|View full text |Cite
|
Sign up to set email alerts
|

Community and Treatment Engagement for Depressed African American Youth: The AAKOMA FLOA Pilot

Abstract: This manuscript focuses on the recruitment efforts and pilot testing of a culturally tailored motivational interviewing intervention associated with the AAKOMA Project, a 2-phase treatment engagement intervention trial for depressed African American adolescents and families. The research team used strategic community engagement as reported in other research derived from AAKOMA. For the pilot study, the research team recruited 23 youth, enrolled 17 youth and randomized 16 of those youth to either the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Thus, treatment engagement strategies that target these behaviors might lead to stronger connections for formal mental health treatment among Black adolescents and their caregivers. For example, negative expectancies might be countered by targeted motivational enhancement strategies that address families’ emotional investment and commitment to change (Breland-Noble 2012; Miller and Rollnick 2002). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, treatment engagement strategies that target these behaviors might lead to stronger connections for formal mental health treatment among Black adolescents and their caregivers. For example, negative expectancies might be countered by targeted motivational enhancement strategies that address families’ emotional investment and commitment to change (Breland-Noble 2012; Miller and Rollnick 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Although a large body of research has documented service need and barriers to treatment among Black adolescents and families (Garland et al 2005; Owens et al 2002; USDHHS 2001), less work has focused on factors that may promote treatment engagement, though research in this area is emerging (Breland-Noble 2012; Breland-Noble et al 2011). In addition, while school mental health services that also involve family members may be an optimal context in which to reach Black adolescents, almost no research has identified the factors associated with successful engagement in school mental health services and that may be amenable to intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, access alone to mental health services has not been found to be the most influential factor for youth of Color to uptake services (Broman, 2012; Brown, 2003). Having trusted providers of Color as well as the recognition of the impact of systemic inequities, such as the stressors of structural racism, have also been noted as integral for families of Color, including youth (Breland-Noble, 2012; Broman, 2012; Brown, 2003; Ford & Airhihenbuwa, 2010; McBride-Murray, Heflinger, Suiter, & Brody, 2011). However, even the studies that incorporate systemic inequities as factors impacting the well-being of youth of Color did not center their actions to achieve a sense of well-being and mental health outside of formal treatment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study concludes that although Black adolescents, including males, assigned to the motivational interviewing intervention had higher attrition rates than the delayed control group, many of these adolescents still initiated depression treatment and reported high rates of consumer satisfaction. Breland-Noble and AAKOMA Project Adult Advisory Board (2012) suggest that the impact of motivational interviewing is more effective, if delivered more immediately.…”
Section: Resultsmentioning
confidence: 99%
“…Peers and friends especially influence YBM’s help-seeking behaviors, for example, they fear friends would tease them about mental health treatment, which increases YBM’s reluctance to share their treatment status (Lindsey et al, 2006; Moses, 2009; Samuel, 2015). Mental health help-seeking for this group, therefore, may be more stigmatizing, and social networks are not likely to be supportive (Breland-Noble & African American Knowledge Optimized for Mindfully Healthy Adolescents [AAKOMA] Project Adult Advisory Board, 2012; Lindsey et al, 2010; Moses, 2009; Samuel, 2015). These help-seeking perspectives may, in part, explain the lower numbers of YBM with depression who actually reach treatment.…”
Section: Conceptualizations Of Help-seeking Treatment Perspectives mentioning
confidence: 99%